2022
DOI: 10.1371/journal.pone.0276540
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study: Improved ratio-in-regression type variance estimator based on dual use of auxiliary variable under simple random sampling

Abstract: In this article, we proposed an improved finite population variance estimator based on simple random sampling using dual auxiliary information. Mathematical expressions of the proposed and existing estimators are obtained up to the first order of approximation. Two real data sets are used to examine the performances of a new improved proposed estimator. A simulation study is also recognized to assess the robustness and generalizability of the proposed estimator. From the result of real data sets and simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Singh and Nigam [22] discussed about the ratio cum product-type exponential estimator in double sampling for stratifcation of the fnite population mean. Ahmad et al [23] proposed an improved ratio-in-regression type variance estimator based on dual use of auxiliary variables under simple random sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Nigam [22] discussed about the ratio cum product-type exponential estimator in double sampling for stratifcation of the fnite population mean. Ahmad et al [23] proposed an improved ratio-in-regression type variance estimator based on dual use of auxiliary variables under simple random sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdizadeh and Zamanzade 11 proposed an interval estimation of the population mean in ranked set sampling. Ahmad et al 12 recommended a new improved generalized class of estimators for population distribution function using the auxiliary variable under simple random sampling. Muhammad et al 13 suggested an enhanced ratio-type estimator for finite population mean using the auxiliary variable in simple random sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Singh et al (2015) developed a chain regression-type estimator for estimating population mean through successive sampling on two occasions, incorporating multi-auxiliary variables. Ahmad et al (2022) put forth an enhanced variance estimator. This novel approach leverages dual auxiliary information to enhance the robustness and generalization of the proposed estimator.…”
Section: Introductionmentioning
confidence: 99%